Creative Thinking: An Islamic Perspective by Jamal Badi and Mustapha Tajdin (Kuala Lumpur: International Islamic University Malaysia 2004. 248 pages.) (American Journal of Islam and Society, 2006)
Growing out of a course that the authors have taught jointly since 1996 atthe International Islamic University Malaysia (“Creative Thinking andProblem Solving”), this book is designed for use as an undergraduate textbookon these issues from an Islamic viewpoint. Since Muslims generally deplore their own community’s lack of creativity and desperately need toreverse their technological and scientific dependence on other countries, theauthors seek to present a realistic strategy to help them regain the innovativespirit that characterized classical Islamic civilization. Drawing on cognitivepsychology and related disciplines in western academia, they begin with theassumption that creativity is a learned skill, rather than the personal endowmentof an elite corps of humanity. The book then develops their secondassumption: Islamic values and perspectives can be enriched through a dialoguewith western social sciences.The first part is devoted to Islamic civilization’s contribution to humancivilization: tafakkur and other Qur’anic words calling for people to thinkcreatively (chapter 1); applying secular “thinking styles” literature to theQur’an, including the inquisitive, objective, positive, hypothetical, rational,reflective/contemplative, visual, metaphorical, analogical, emotional, perceptual,conceptual, intuitive, scientific, and wishful thinking styles (chapter2); analyzing the concept of ijtihad and its vocation to constantly adaptIslamic law to changing circumstances and find creative solutions to persistentsocioeconomic and political challenges (chapter 3); and summarizingMuslim contributions to science, philosophy, and medicine (chapter 4) ...